Political economy of modern capitalism : mapping convergence and diversity - Crouch, Colin, 1944-; Streeck, Wolfgang, 1946- (Sage, 1997)
'Political Economy and Modern Capitalism' provides a practical and informed analysis of the public policy choices facing governments and business around the world.